2020
DOI: 10.3390/su12062441
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Bandwagon Consumption Behavior Based on Fear of Missing Out and Product Characteristics

Abstract: There have been unusual collective consumption phenomena that consumer behavior conforms to as part of the pursuit of specific brands (e.g., teenagers wearing the same brand jacket). In order to explain bandwagon consumption behavior, previous studies focused on brand, personal traits, and group characteristics. However, previous studies seem somewhat limited in explaining excessive bandwagon consumption. This study addresses a psychological trait, the Fear of Missing out (FoMO), which describes why people wan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…When this is the case, the consumption pattern usually follows the conformity trend. The results echo findings by Kang and Ma (2020) . They found teenagers often wear the same brand jacket.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…When this is the case, the consumption pattern usually follows the conformity trend. The results echo findings by Kang and Ma (2020) . They found teenagers often wear the same brand jacket.…”
Section: Discussionsupporting
confidence: 85%
“…According to the relevant studies, the role of conformity was also measured by a five-item scale: ① I associate with students who have the same levels of consumption as mine; ② My good friends are those who share my purchase and consumption habits, for example in the choice for brands of clothing, cosmetics, mobile phones, etc. ; ③ Conformity mentality takes over in my buying decision process; ④ I compare my consumption behavior to that of my classmates’; ⑤ I feel ashamed and fear being looked down upon when I do not have goods my classmates have, for example phones, computers and watches of a certain brand ( Kang and Ma, 2020 ). Respondents evaluated the abovementioned two five-item scales using a nine-point Likert-type scale where 1 means completely disagree, while 9 means completely agree.…”
Section: Methodsmentioning
confidence: 99%
“…This analysis is supported according to the antecedents identified in the literature, which establishes that the periods of exposure to the media are relevant to offer more assertive conclusions about how risk communication affects perceived risk (Faour-Klingbeil et al, 2021;Zhang, 2021;Barrelet et al, 2013aBarrelet et al, , 2013bHeydari et al, 2021;Freimuth et al, 2008;Karasneh et al, 2020). Besides, other studies detail that depending on the time of exposure to a medium, the bandwagon effect produces more consumption (Choi et al, 2015;Kang and Ma, 2020), and the perception of demand-framed scarcity leads to higher purchase intention, where psychological risk underlies these effects (Huang et al, 2020). To conduct this analysis, participants were asked how much time they spent on COVID-19 risk communication exposure one week before implementing the social distancing measures.…”
Section: Discussionmentioning
confidence: 55%
“…The bandwagon effect is a type of cognitive bias that can manifest itself in various forms of consumption, because it involves group norms, the need for belonging and acceptance (Shaikh et al , 2017; Tynan et al , 2010; Nadeau et al , 1993). The literature has identified that with greater exposure of messages, the bandwagon effect produces more consumption (Choi et al , 2015; Kang, and Ma, 2020), where it even makes luxury products available to all consumers (Bahri-Ammari et al , 2020). The literature does not offer studies covering how the bandwagon effect becomes a consumer way of managing risk.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Indoor spatial ambience has a significant influence in the decision-making process and consumption behavior of consumers. For different spatial ambience preferences and importance, solutions are designed to meet the needs of different consumers [1][2]. It is very important for investors, operators, and designers to set a comfortable and safe commercial space design positioning that is favored by the target consumer market.…”
Section: Introductionmentioning
confidence: 99%